Implementation of Principal Academic Supervision in Improving Teacher Performance - Rawati Rawati; Murniati Murniati; Niswanto Niswanto (STAI Hubbulwathan Duri, 2022)
This study aimed to elicit empirical evidence regarding the effectiveness of principal academic supervision in enhancing teacher performance at Madrasah Tsanawiyah Aceh Barat Daya. It also determines how the execution of the principal's academic supervision affects teacher performance and hence the quality of education. Qualitative research was used in this study. The researchers employed a descriptive method in conjunction with a phenomenological qualitative approach to investigate a social phenomenon or human problem in this study. The data gathering strategies used in this study were structured interviews, observation, and documentation. Academic supervision of the principal at Madrasah Tsanawiyah in Aceh Barat Daya occurred according to the implementation plan, the material being coached, the implementation results, and the feedback from academic supervision implementation to improve the performance of class teachers.